POTENTIAL AND UTILIZATION LEVEL OF KRAI TUNA (Auxis thazard) LANDED AT SIBOLGA ARCHIPELAGO FISHING PORT NORTH SUMATERA PROVINCE - Pubra, Rina Ade Citra; Brown, Arthur; Yani, Alit Hindri (Asian Journal of Aquatic Sciences, 2024)
Krai tuna (Auxis thazard) is the most dominant catch in Sibolga Archipelago Fishing Port and has economic value, so the community widely consumes it. The magnitude of the potential of fisheries in Sibolga makes it important to analyze the stock of krai for the development and processing of the capture fisheries sector. The research method used is the survey method, the data needed is secondary data in the form of catch data and fishing effort for seven years (2016-2022), the data analysis used is the surplus production method with the Schaefer and Fox model approach, From the results of the study, it was concluded that the sustainable potential of krai using the production surplus approach method is more suitable using the Schaefer approach model because it has a low JTB of 1508 tons with a utilization rate status of 98.94% and is already in a fully-exploited condition or has reached the saturation point (catch-intensive). Utilization is almost near saturation point, so it is necessary to reduce fishing effort so that the catch remains and stock availability is maintained.